Risk, reliability and safety : innovating theory and practice : proceedings of ESREL 2016 (Glasgow, Scotland, 25-29 September 2016) /: innovating theory and practice : proceedings of ESREL 2016 (Glasgow, Scotland, 25-29 September 2016). (2016) - Unknown
No abstract available